(3GdLhgQ GdfVjO aj TQM cJGH GdJLQjOs - (3GdMdis; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3GeG HYO aEf Gddg JYGdi deG habfi ddGSJaGOI ef TjNfG s
(3BNQgG (B:s
(3cdeG cGfJ CZQH cGfJ CdP hCYLH adGjecf VHWgG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs